Prioritizing Sustainability Criteria in Urban Planning Processes: Methodology Application - Wallbaum, Holger; Krank, Sabrina; Teloh, Rolf (Journal of Urban Planning and Development, 2011)
Since the beginning of the sustainability debate approximately 20 years ago, all parties involved in the urban planning process have been expected to devise sustainable solutions to meet the challenges of the 21st century. Potential to include sustainability criteria is present in the strategic planning stage and during the initial studies of a project. However, instruments available at these early stages are rare and show numerous weaknesses. The present study intends to close this gap by developing an instrument for the prioritization of sustainability criteria in urban planning processes. It is based on the Sustainable Building Tool 07 (SBTool 07), a comprehensive and well-established tool for the assessment of sustainability of construction projects, key issues pertaining to the initial planning stages are identified via a materiality matrix—a method established for corporate sustainability reporting. The resulting method has been tested in a competition in the Icelandic city of Reykjavík. Results include a materiality matrix on stakeholder priorities and the relevance of criteria to sustainability across the life cycle as well as a core set of 19 criteria to be addressed in Reykjavík.